2016
DOI: 10.1093/geronb/gbw049
|View full text |Cite
|
Sign up to set email alerts
|

Leisure Activity Engagement and Positive Affect Partially Mediate the Relationship Between Positive Views on Aging and Physical Health

Abstract: Leisure activity engagement and positive affect were shown to help explain the relationship between PVA and health, but differently for different health constructs and also among middle-aged and older adults. Findings provide further insight into ways in which PVA influence health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…The successful aging model highlights the process of adaptation to health challenges as described in the selective optimization with compensation model (Baltes & Baltes, 1993). People with a higher sense of control over personal health through information acquisition and/or better self-care practices have significantly slower rates of health-related decline over time (Kempen, Ranchor, van Sonderen, van Jaarsveld, & Sanderman, 2006; Hicks & Siedlecki, 2017). Obtaining health information from online sources is a proactive behavioral adaptation to health challenges that increase in later life (Cotten, Ford, Ford, & Hale, 2012; Drentea, Goldner, Cotten, & Hale, 2008; Stowe & Cooney, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The successful aging model highlights the process of adaptation to health challenges as described in the selective optimization with compensation model (Baltes & Baltes, 1993). People with a higher sense of control over personal health through information acquisition and/or better self-care practices have significantly slower rates of health-related decline over time (Kempen, Ranchor, van Sonderen, van Jaarsveld, & Sanderman, 2006; Hicks & Siedlecki, 2017). Obtaining health information from online sources is a proactive behavioral adaptation to health challenges that increase in later life (Cotten, Ford, Ford, & Hale, 2012; Drentea, Goldner, Cotten, & Hale, 2008; Stowe & Cooney, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In this investigation, older adults with positive self-perception of life as well as those with dancing habits presented less clinical-functional vulnerability, probably because they developed successful trajectories in aging, with particular attention to the variable of "dancing habits" associated with robustness between long-lived older adults (80 years or older) and young-old adults (60 to 79 years). The literature also showed that older adults capable of managing their own life (autonomy) and performing leisure activities revealed a self-perception of optimistic life, which contributes to a healthy and active old age 1,2,[23][24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…Another significant point related to healthy longevity was the fact that the older population with cognitive and functionally independent abilities acquire healthy behaviors throughout life 2,24,26,29 and can even enjoy digital technology in health management 30 . Such statement reiterates the findings of this research, in which the interviewees considered robust showed a higher prevalence of walking habits, as well as absence of cognitive impairment or depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This framework focuses on how productive activity in retirement -such as paid work, volunteering, or caregiving -is favourable for individuals and for society (Morrow-Howell & Wang, 2013). Productive aging is a sharp contrast to earlier conceptualizations of retirement that underscored decline and isolation (Butler & Gleason, 1985;Morrow-Howell, Hinterlong, & Sherraden, 2001;O'Reilly & Caro, 1995) and is also a contrast to cultural depictions of the "golden years" that represent retirement as a time to enjoy life without the burdens of work (Hicks & Siedlecki, 2017). Productive aging has been criticized for imposing negative judgements on older adults who fail to engage in economically productive activity for a variety of reasons including declining health or caregiving obligations (Bülow & Söderqvist, 2014;Dillaway & Byrnes, 2009;Holstein, 1993;Martinson & Halpern, 2011).…”
Section: Theoretical Frameworkmentioning
confidence: 99%